Psychological Well-Being and Quality of Life among Older Adults in Jakarta Nursing Homes: A Scoping Review - Andry Yanti; Anjani Arum Safitri; Fitria Rahayu; Aneuke Yu'dzia Mirzalline; Tsabitha Azzahra; Izatul Himmiyah (Yayasan Sembilan Pemuda Indonesia, 2027)
This scoping review maps available evidence on psychological well-being and quality of life among older adults in Jakarta nursing homes, identifies contributing factors, examines measurement instruments, and determines research gaps requiring further investigation. Following the Joanna Briggs Institute framework and PRISMA-ScR approach, six databases were searched for peer-reviewed publications (2021–2026). Of 113 records identified, 26 duplicates were removed, 87 titles/abstracts were screened, 31 full texts were assessed, and two studies met the strict Population-Concept-Context criteria, involving 252 older adults from two public nursing homes in Jakarta. Social support, loneliness, depression, anxiety, and sleep quality emerged as prominent determinants. Loneliness demonstrated strong negative relationships with psychological well-being and perceived social support, while anxiety was the dominant predictor of poorer quality of life, followed by depression and sleep disturbance. This review uniquely focuses on institutionalized older adults in Jakarta and identifies a substantial evidence gap: very few studies explicitly assess psychological well-being or quality of life using standardized instruments in this setting. Findings support routine psychosocial screening, structured peer-support activities, and integrated anxiety and depression management in nursing homes. This review provides a foundational evidence synthesis for policymakers and healthcare providers, highlighting critical research gaps and offering actionable recommendations to improve mental health services for institutionalized older adults in Jakarta.